Reasons for reported suspicion of child maltreatment and responses from the child welfare - a cross-sectional study of Norwegian public dental health personnel - Ingfrid Vaksdal Brattabø; Ragnhild Bjørknes; Anne Nordrehaug Åstrøm (BMC, 2018)
Abstract Background To prevent child maltreatment, the identification of vulnerable children is essential. In Norway, public dental health personnel (PDHP) report suspicion of child maltreatment to child welfare services (CWS) at a relatively high rate. However, their reasons for reporting and the response from CWS have not been investigated. The objectives of this study were to (1) explore the reasons that PDHP send reports of concern, (2) examine how CWS responds to PDHP reports, and (3) assess whether different reasons for concern are associated with a given response from CWS. Methods A national cross-sectional study was conducted by an electronic survey distributed to public dental hygienists and dentists in Norway. Descriptive statistics were calculated in terms of mean (SD) distributions and frequency, expressed as % (n). To account for clustering of responses among respondents, binomial generalized estimating equation analysis was used to estimate odds ratios (ORs) and confidence intervals (CIs) of CWS responses across number of reports with different reasons for concern. Results Of a total of 1542 questionnaire recipients, 1200 (77.8%) responded to the survey. From 2012 to 2014, 42.5% of the respondents sent 1214 reports to CWS, with a mean number of 2.7 (SD = 2.0) reports per respondent. The PDHP sent the reports due to suspicion of neglect or physical, sexual and/or psychological abuse. Non-attendance at dental appointments and grave caries were reported most frequently. Among the reports, 24.5% resulted in measures being taken by CWS, 20.7% were dropped, and 29.4% lacked information from CWS on the outcome. Reports due to suspicion of sexual abuse, (OR 1.979, 95% CI (1.047-3.742), P = 0.036), grave caries (OR 1.628, 95% CI (1.148-2.309), P = 0.006), and suspicion of neglect (OR 1.649, 95% CI (1.190-2.285), P = 0.003) had the highest association with the implementation of measures. Conclusions PDHP report on several forms of child maltreatment and contributes in detection of victimized children. However, the relatively low number of measures being taken by CWS and the number of reports that lack a response to reporters reveal a need for a closer cooperation between the services, as this would benefit both the children at risk and the services.